Manajemen Asuhan Keperawatan Keluarga dengan Masalah Hipertensi: Fokus pada Pemeliharaan Kesehatan dan Penguatan Koping Keluarga - nurma zela gustina; Naila Alya Muhbita (Awatara Publisher, 2026)
Background: Hypertension is a global health challenge requiring sustainable self-management at the family level. Non-adherence to medical therapy and maladaptive coping patterns are often major barriers to blood pressure control, risking chronic cardiovascular complications. Objective: This study aims to describe the family nursing care for Mr. R (49 years old) with a focus on strengthening health maintenance and optimizing family coping strategies. Methods: This study used a case report design with a family nursing process approach during three home visits. Data were collected through interviews, environmental observations, and physical examinations, and analyzed using the problem priority scoring method. Results: The primary nursing diagnoses were ineffective health maintenance and compromised family coping. Interventions included health education on the DASH diet, smoke-free home environment modification, and coping counseling to improve communication openness. Evaluation results showed an increase in family independence in performing five family health tasks, marked by a commitment to utilize national health insurance (BPJS) for routine check-ups and improvements in affective coping patterns. Conclusion: A participatory family nursing approach is effective in changing health behaviors and strengthening the family's internal support system in hypertension management.